Effects of global value chains on energy efficiency in G20 countries - Luo, Heng; Sun, Ying; Tao, Xiaosha; Tan, Wenwu; Kamarudin, Fakarudin (Elsevier, 2024)
Participation in global value chains brings both opportunities and challenges for the global energy sector. Using country-level panel data of G20 economies from 1990 to 2018, this study examines the influence of global value chains on energy efficiency. The results indicate that global value chains participation has a promotion effect on energy efficiency. Quantile regression results reveal that the positive effect is more pronounced in countries with lower efficiency. Additionally, the moderator analysis results show that high institutional quality can amplify the impact of global value chains. Mediator analysis results demonstrate that global value chains can enhance energy efficiency by optimising industrial structures and improving energy structures. When geopolitical risk exceeds the threshold value, the effect of global value chains is even greater. Finally, the study also suggests some policy implications.